Pulsatile Drug Delivery System Utilizing Innovative Technology - Mayssam Hussein, Israa Nathir (Pakistan Journal of Medical & Health Sciences, 2022)
Drugs might be released immediately or over time. Pulsatile medication release systems, on the other hand, have been increasing in popularity in recent years. Many medications or therapies could benefit from pulsatile drug release, in which the drug is released rapidly after a predetermined lag time. Pulsatile release systems come in pairs: multi and separate pulse. Rupturable dose forms are a prominent type of single-pulse device. Other methods have a drug-containing centre covered by both a swelling surface and a semi - permeable barrier polymer layer or membrane that is semipermeable but not soluble. The full action of the swelling film, and the permeability and mechanical qualities of the polymer covering, have a large impact in the lag time before the rupture. Many significant features in living organisms are controlled either by pulse or temporary release of active ingredients at a particular spot and duration. As a result, innovative drug delivery systems must be created to accomplish pulsed dispersion of a specified quantity of drugs in simulating the action of organisms while reducing adverse reactions. Special emphasis has been paid to the thermolabile poly (N-isopropylacrylamide) and its derivatives hydrogels. Designing drug delivery devices, hydrogels, and other materials. Micelles allows for thermal stimuli-regulated pulsed drug release. So, pulsatile medication delivery is one of those systems that has a lot of promise for people with long-term conditions like arthritis, asthma, and high blood pressure because it gives drugs at the right time, in the right place, and in the right amount.